Bronchoalveolar-Lavage-Derived Fibroblast Cell Lines Provide Tools for Investigating Various Interstitial Lung Diseases - Siri Lehtonen; Riitta Kaarteenaho (Cells, 2022)
Bronchoalveolar lavage (BAL) is an important diagnostic and research tool for the investigation of various lung diseases. In addition to inflammatory and epithelial cells, BAL fluid may contain a small number of stromal cells, such as fibroblasts. During the past 30 years, a number of research groups have cultured BAL-derived fibroblasts for several passages in vitro. In addition to fibroblasts, these cultures have been reported to contain fibrocytes, myofibroblasts, and stem cells. We aim to present a summary of studies that have cultured stromal cells from BAL fluid.